2018
DOI: 10.1155/2018/4829023
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Neural Tube Defects and Associated Risk Factors at Three Teaching Hospitals in Addis Ababa, Ethiopia

Abstract: There is scarcity of data on prevalence of neural tube defects (NTDs) in lower-income countries. Local data are important to understand the real burden of the problem and explore risk factors to design and implement preventive approaches. This study aimed to determine prevalence and risk factors of NTDs. A hospital-based cross-sectional and unmatched case-control study was conducted at three teaching hospitals of Addis Ababa University. NTDs were defined as cases of anencephaly, spina bifida, and encephalocele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
122
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(144 citation statements)
references
References 30 publications
19
122
3
Order By: Relevance
“…The highest burden of NTDs was observed in Adigrat Hospital from Eastern Zone (174 per 10,000 live and stillbirths) and southern zone of Tigray (304 per 10,000 live and stillbirth). Similar findings were reported from prospective studies of births at three teaching hospitals in Addis Ababa, Ethiopia with 126 per 10,000 births [ 19 ]. Folate deficiency is widespread in Ethiopia.…”
Section: Discussionsupporting
confidence: 87%
“…The highest burden of NTDs was observed in Adigrat Hospital from Eastern Zone (174 per 10,000 live and stillbirths) and southern zone of Tigray (304 per 10,000 live and stillbirth). Similar findings were reported from prospective studies of births at three teaching hospitals in Addis Ababa, Ethiopia with 126 per 10,000 births [ 19 ]. Folate deficiency is widespread in Ethiopia.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the studies were conducted in the central and northern part of the country. All studies were cross-sectional studies 23,24,26,27,29,31,[37][38][39] except a cohort study conducted in Tigray. 36 All of the studies were conducted Abbreviations: OR, odds ratio; CI, confidence interval; BMI, body mass index; NA, not applicable; DD, dietary diversity; BF, breast feeding; PX, pregnancy.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…24 It is also stated in other primary surveys in Ethiopia that there are sizeable numbers of pregnancies associated with NTDs. 20,[25][26][27][28][29][30][31][32] These findings are inconsistent and inconclusive for policy makers and stakeholders. Therefore, the pooled prevalence, patterns, and risk factors for NTDs in Ethiopia were explored in this systematic review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of NTDs in Canada is approximately 4 per 10 000 live births; this decreased from 7.6 per 10 000 births following the initiation of folate fortification of grain products in 1998 to prevent folate‐deficiency‐related NTDs . Although data are limited, studies globally have shown substantial geographic variability in rates of NTDs from 5.2 per 10 000 live births to more than 120 per 10 000 live births in African countries …”
Section: Introductionmentioning
confidence: 99%